Optimized T-shaped soil-cement deep mixing column for sustainable ground improvement - Yao, Kai; Singh, Moirangthem Johnson; Rong, Yu; Yao, Zhanyong (Frontiers in Built Environment, 2025)
Since the introduction of Deep Cement Mixing (DCM) technology, it has been widely applied to enhance the strength and stability of problematic soil. Among its advancements, the T-shaped DCM column has emerged as an innovative solution in large-scale infrastructure and urban projects. It offers several benefits, including enhanced bearing capacity while significantly reducing settlement in soft ground. This study focuses on optimizing the T-shaped DCM column while ensuring its mechanical strength remains intact through a comprehensive numerical analysis. This study considers three different column types: the conventional DCM, the T-shaped DCM, and the T-shaped column with varied strength. The analysis reveals that the lower portion of the column plays a less significant role in the overall bearing capacity, indicating potential for optimization that could effectively reduce construction costs for the T-shaped DCM column. It is essential to observe that failures in both the T-shaped and varied-strength columns primarily occur at the head and the uppermost section of the body. Notably, the varied-strength T-shaped DCM exhibits a bearing capacity that is two to three times greater than that of the conventional DCM column. Furthermore, the varied-strength column is distinguished by its notably lower construction costs compared to its counterparts. This design alternative is promising, as it maintains a higher bearing capacity and exhibits reduced settlement compared to the conventional DCM, making it a feasible choice for practical field applications.